A role for p38 MAP kinase in platelet activation by von Willebrand Factor - Canobbio, Ilaria; Reineri, Stefania; Sinigaglia, Fabiola; Balduini, Cesare; Torti, Mauro (Thrombosis and Haemostasis, 2004)
Platelet activation induced by von Willebrand factor (VWF) binding to the membrane GPIb-IX-V receptor involves multiple signal transduction pathways. Among these, recruitment and activation of the FcγRIIA and stimulation of phospholipase A2 represent independent events equally essential to support a complete platelet response. Phospholipase A2 is activated by calcium and by phosphorylation through MAP kinases. In this work, we found that VWF stimulated the rapid and sustained phosphorylation of p38 MAP kinase (p38MAPK). In vitro kinase assay revealed that VWF-stimulated phosphorylation of p38MAPK was associated with increased kinase activity. Binding of VWF to GPIb-IX-V, but not to integrin αIIbβ3, was required to support phosphorylation of p38MAPK. Neither the blockade of the membrane FcγRIIA by a specific monoclonal antibody or the prevention of thromboxane A2 synthesis by cyclooxygenase inhibitors affected VWF-induced p38MAPK activation. However, phosphorylation of p38MAPK was prevented by the tyrosine kinase Syk inhibitor piceatannol. Treatment of platelets with the p38MAPK inhibitor SB203580 totally prevented VWFstimulated platelet aggregation. Moreover, release of arachidonic acid induced by VWF was strongly impaired by inhibition of p38MAPK. We also found thatVWF induced phosphorylation of cytosolic phospholipase A2, and that this process was prevented by the p38MAPK inhibitor SB203580.These results demonstrate that p38MAPK is a key element in the FcγRIIA-independent pathway for VWF-induced platelet activation, and is involved in the stimulation of phospholipase A2 and arachidonic acid release.
Keywords: p38 MAP kinase; von Willebrand Factor; tyrosine phosphorylation; phospholipase A2; arachidonic acid